Cyclical behavior of debt and equity using a panel of Canadian firms - Francisco Covas; Wouter J. den Haan (Bank of Canada, 2007)
We document the cyclical behavior of debt, equity, and retained earnings for different firm categories using firm-level Canadian data. There is evidence of both procyclical equity and debt issuance for all firm categories but the timing differs. In particular, there is strong evidence that equity issuance increases in anticipation of an expansion. During this phase, some substitution between debt and equity takes place. After the expansion has reached its peak, equity issuance starts to decrease and during this phase there is strong evidence of procyclical debt issuance and some substitution out of equity seems to take place. Retained earnings is procyclical except for small firms.
Keywords: E32; G32; 330; Business fluctuations and cycles; Konjunktur; Betriebliche Finanzwirtschaft; Eigenkapital; Fremdkapital; Kapitalerhöhung; Kanada